2013
DOI: 10.1177/0892705712475019
|View full text |Cite
|
Sign up to set email alerts
|

Composites from recycled polypropylene and rubberwood flour

Abstract: The mechanical properties of composites from recycled waste plastic and waste sawdust are of interest in trying to convert these waste streams to useful products. The development of these composites from natural fiber is therefore receiving widespread attention due to the growing environmental awareness. The effects of compositions were investigated including different grades of plastic (virgin and recycled) and amounts of wood flour, coupling agent, and ultraviolet (UV) stabilizer on mechanical and physical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…High wood flour content increases the modulus of elasticity (MOE) of composites, 31 so that higher stress is required for the same deformation. 7,32 The choice of MAPP content between 3 and 5 wt% barely affected the C e . Generally, the addition of coupling agent in the WPCs decreases the creep strain due to the improved filler dispersion and improved interfacial adhesion between wood flour and polymer matrix, [33][34][35] whereas too much MAPP relative to wood flour will cause selfentanglement, resulting in slippage with the PP molecules.…”
Section: Homkhiew Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…High wood flour content increases the modulus of elasticity (MOE) of composites, 31 so that higher stress is required for the same deformation. 7,32 The choice of MAPP content between 3 and 5 wt% barely affected the C e . Generally, the addition of coupling agent in the WPCs decreases the creep strain due to the improved filler dispersion and improved interfacial adhesion between wood flour and polymer matrix, [33][34][35] whereas too much MAPP relative to wood flour will cause selfentanglement, resulting in slippage with the PP molecules.…”
Section: Homkhiew Et Almentioning
confidence: 99%
“…6 Most of the wood waste can be used in medium-density fiberboard and particle board. 7 However, the use of wood waste as reinforcement in plastic composites is of great interest, with environmental and economic benefits. The advantages of wood particles include biodegradability, low health hazard during handling, and non-abrasive nature, 8,9 when substituted for synthetic fillers such as glass fiber, carbon fiber, and other inorganic fillers.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the nonuniform spatial distribution of wood flour, polymer, and UV stabilizer. 9,34 When WPCs experienced with the nonuniform spatial distribution and poor interfacial adhesion between the compositions, it allows easier access of water into the structure. Figure 3 displays the numerically optimized composition, based on these model fits.…”
Section: Effect Of Composition On Wa and Optimal Formulationmentioning
confidence: 99%
“…14,15 Natural fibers have successfully improved the mechanical properties of plastic composites, as the following examples demonstrate. Homkhiew et al 9 investigated the effects of rubberwood content on the mechanical properties of recycled PP composites and found that the modulus and hardness of composites increased linearly with an increase of wood flour loadings in the range of 25-45 wt% wood flour. Karmarkar et al 16 also reported that the tensile strength and modulus linearly increased with an increase of wood fiber from 10 to 50 wt% in PP composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation